Vertical sleeve gastrectomy normalizes circulating glucocorticoid levels and lowers glucocorticoid action tissue-selectively in mice - Akalestou, Elina; Lopez-Noriega, Livia; Christakis, Ioannis; Hu, Ming; Miras, Alexander D.; Leclerc, Isabelle; Rutter, Guy A. (Frontiers in Endocrinology, 2022)
Objectives Glucocorticoids produced by the adrenal cortex are essential for the maintenance of metabolic homeostasis. Glucocorticoid activation is catalysed by 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1). Excess glucocorticoids are associated with insulin resistance and hyperglycaemia. A small number of studies have demonstrated effects on glucocorticoid metabolism of bariatric surgery, a group of gastrointestinal procedures known to improve insulin sensitivity and secretion, which were assumed to result from weight loss. In this study, we hypothesize that a reduction in glucocorticoid action following bariatric surgery contributes to the widely observed euglycemic effects of the treatment. Methods Glucose and insulin tolerance tests were performed at ten weeks post operatively and circulating corticosterone was measured. Liver and adipose tissues were harvested from fed mice and 11β-HSD1 levels were measured by quantitative RT-PCR or Western (immuno-) blotting, respectively. 11β-HSD1 null mice (Hsd11b1-/-) were generated using CRISPR/Cas9 genome editing. Wild type and littermate Hsd11b1-/- mice underwent Vertical Sleeve Gastrectomy (VSG) or sham surgery. Results Under the conditions used, no differences in weight loss were observed between VSG treated and sham operated mice. However, both lean and obese WT VSG mice displayed significantly improved glucose clearance and insulin sensitivity. Remarkably, VSG restored physiological corticosterone production in HFD mice and reduced 11β-HSD1 expression in liver and adipose tissue post-surgery. Elimination of the 11β-HSD1/Hsd11b1 gene by CRISPR/Cas9 mimicked the effects of VSG on body weight and tolerance to 1g/kg glucose challenge. However, at higher glucose loads, the euglycemic effect of VSG was superior to Hsd11b1 elimination. Conclusions Bariatric surgery improves insulin sensitivity and reduces glucocorticoid activation at the tissular level, under physiological and pathophysiological (obesity) conditions, irrespective of weight loss. These findings point towards a physiologically relevant gut-glucocorticoid axis, and suggest that lowered glucocorticoid exposure may represent an additional contribution to the health benefits of bariatric surgery.